The Influence of Word of Mouth, School Facilities, and School Programs on Parents School Choice Decisions - Dian Wahyuningtyas; Ike Kusdyah Rachmawati; Yunus Handoko (Al-Qalam Institue, 2026)
facilities, and school programs on parents’ school choice decisions. The research employed a quantitative approach using a survey method. The population consisted of parents of students enrolled at a private junior high school, with a total of 47 respondents selected using a saturated sampling technique. Data were collected through structured questionnaires and analyzed using multiple linear regression with the assistance of SPSS version 26. The results indicate that word of mouth has a positive and significant effect on parents’ school choice decisions. In contrast, school facilities and school programs do not show a significant partial effect. However, the simultaneous test reveals that word of mouth, school facilities, and school programs collectively have a significant influence on parents’ decisions in choosing a school. These findings suggest that interpersonal communication and recommendations play a more decisive role than physical facilities or program offerings in parents’ school evaluations. This study contributes to the literature on educational service marketing by emphasizing the importance of word of mouth as a key determinant of parents’ school choice decisions and provides practical implications for school management in developing effective communication and promotional strategies.